Human Capital Development, Poverty and Economic Growth in Nigeria - Jerry, Joseph; Angahar, Jacob Sesugh; Terzungwe, Kokoh Simon (Darul Yasin Al Sys, 2025)
This study investigates the impact of human capital development on poverty reduction and economic growth in Nigeria. Utilizing a time series analysis from 1990 to 2023, the study aims to understand the relationship between key human capital indicators education, healthcare, and social welfare and their influence on poverty alleviation and economic growth. The analysis incorporates data from various sources, including the World Bank and Nigeria's National Bureau of Statistics, to evaluate the trends and effectiveness of human capital investments over three decades. Autoregressive distributive Lag model (ARDL) was used as a method of analysis. The findings reveal a significant positive correlation between human capital development and economic growth, indicating that increased investment in education and healthcare leads to higher economic output. Moreover, the study identifies a strong inverse relationship between human capital development and poverty rates, suggesting that improvements in education and healthcare access substantially reduce poverty levels. Specifically, periods with higher government spending on education and healthcare correspond to noticeable declines in poverty and enhancements in GDP growth. However, the study also highlights persistent challenges, such as regional disparities, insufficient funding, and policy implementation gaps, which hinder the full realization of human capital development benefits. These issues underscore the need for a more coordinated and integrated policy approach to align economic growth strategies with human capital development goals. Based on these findings, the study recommends several policy actions: increased investment in education and healthcare, targeted social programs for poverty alleviation, and enhanced policy coordination, promotion of inclusive economic growth, inflation control measures, strengthening of social protection systems, and improved data collection and research efforts. Implementing these recommendations could significantly boost Nigeria's human capital development, reduce poverty, and foster sustainable economic growth.